Lateral performance of a Pres-Lam frame designed for gravity loads. (1st September 2016) - Smith, Tobias; Watson, Chris; Moroder, Daniel; Pampanin, Stefano; Buchanan, Andy
Graphical abstract: Highlights: A Pres-Lam frame designed to resist gravity loading has been tested horizontally. The Pres-Lam gravity frame contributed significantly to lateral resistance. External steel was added to the frame increasing strength and energy dissipation. Analytical procedures have been proposed to assess the lateral strength. Abstract: This paper analyses the lateral load performance of a post-tensioned timber (Pres-Lam) frame which was designed with the primary function of supporting gravity loading. A full scale, two bay frame was used and subjected to quasi-static horizontal displacement. A total of four tests were performed, one with only the post-tensioning cables to resist horizontal loading and three with the addition of sacrificial steel elements externally attached and acting as dissipative reinforcing. This external reinforcing increased the moment capacity of the frame connections and the ability of the frame to release energy through hysteretic damping. Following a description of the test setup the results show that although the primary functions of the post-tensioning is to reduce section height and increase bay length under gravity loading it will also provide a significant contribution to the lateral resistance of the structure. Finally, a simplified design procedure is presented which allows assessing the magnitude of this contribution.